Thin-section CT of midbrain abnormalities in progressive supranuclear palsy. - Masucci, E F; Borts, F T; Smirniotopoulos, J G; Kurtzke, J F; Schellinger, D (American Journal of Neuroradiology, 1985)
Thin-section computed tomographic (CT) scans of 3 and 1.5 mm thickness were obtained using the Philips Tomoscan 310 and General Electric 8800 CT/T scanners in the study of 10 consecutive patients with progressive supranuclear palsy (PSP) and 31 patients with other diseases. Marked midbrain and moderate pontine atrophy, a dilated third ventricle, and enlarged quadrigeminal plate cisterns were observed in all PSP cases. The aqueduct was dilated in several. In six of the PSP cases, there was a striking midbrain abnormality in the form of a low-density area extending from the interpeduncular cistern toward the aqueduct. Thin-section metrizamide-enhanced cisternography of three of the six PSP cases showed that the low-density abnormality was the result of the interpeduncular cistern invaginating the atrophic midbrain.